出版物盗版在中国 ：经济成因及基本对策研究 = Publication piracy in China : economic analysis and countermeasures - 冯 韶慧 Feng, Shaohui (2008)
This thesis attempts to apply various methods including the cost analysis to analyze the current situation of piracy problem in China and to evaluate the effect of various anti-piracy policies and instruments.